Social critique and viewer's response in the Italian Gangster film: the case of Bandits in Milan (1968) and Romanzo Criminale (2005). Issue 3 (1st September 2020) - Paoli, Marco; Pezzotti, Barbara
ABSTRACT: This article investigates the development of the Italian gangster film and its interconnections with film noir. Specifically, this article will focus on those cinematic manifestations' attempts to explore post-war Italian culture, society and political context through the portrayal of some of the most important Italian criminal figures of this period. It argues that, while sharing some characteristics such as the femme fatale, flashback structures and a narrative of betrayal, like its American counterpart the Italian gangster film also presents a flexibility that show the mutative qualities of the genre. In order to prove this point, this article analyses two gangster films: Carlo Lizzani's Bandits in Milan (1968) and Michele Placido's Romanzo criminale (2005) also through the lens of the viewer's process of identification. By showing how the protagonists and their victims are represented in these films, and how this intersects with the social critique featured in these films, this article revaluates the Italian gangster film as a creative and artistic output that should be analysed beyond its generic conventions.